Melatonin reduces the expression of alpha-synuclein in the dopamine containing neuronal regions of amphetamine-treated postnatal rats - Kwankanit Sae-Ung (2018)
Alpha-synuclein (α-syn) is a neuronal protein that is involved in various degenerative disorders such as Parkinson's disease. It is found in the presynaptic terminals and perinuclear zones of many brain regions. Amphetamine (AMPH), a psychostimulant drug abused progressively more commonly in recent years, has been known to induce neurotoxicity in the central dopaminergic pathway, which is associated with increased oxidative stress. Recently, AMPH has been shown to significantly increase the level of α-syn in dopaminergic neuroblastoma cell cultures. Melatonin is recognized as an antioxidant for the nervous system. This study tested whether melatonin can attenuate the effect of AMPH on the expression of α-syn in the dopaminergic pathway of the neonatal rat. Four-day old postnatal rats (P4) were injected subcutaneously with either AMPH (increasing dose, 5-10 mg/kg daily) alone or AMPH with melatonin (2 mg/kg) daily at 10:00 AM for 7 consecutive days. As determined using Western blot, the level of α-syn was significantly increased in the substantia nigra, dorsal striatum, nucleus accumbens, and prefrontal cortex of the AMPH-treated group, while melatonin treatment either prior to AMPH or alone decreased the accumulation of the protein to 77%, 96%, 78%, and 77% of the control value, respectively. Furthermore, an immunofluorescent study showed that the α-syn-immunoreactivity increased noticeably in the nuclei of cell bodies and nerve terminals of the AMPH-treated group. Again, melatonin lowered this immunoreactivity. These results indicate that melatonin has a direct or indirect effect in reducing the expression of α-syn in the postnatal rat. The exact mechanism of this mitigation should be further investigated. © 2011 John Wiley & Sons A/S.